2012
DOI: 10.1089/cyber.2011.0403
|View full text |Cite
|
Sign up to set email alerts
|

Self-Disclosure Among Bloggers: Re-Examination of Social Penetration Theory

Abstract: Based on Social Penetration theory, this study explores the topics that bloggers disclose on their blogs, and in the real world. A total of 1,027 Taiwanese bloggers participated in this online survey, which revealed that bloggers self-disclosed nine topics (attitude, body, money, work, feelings, personal, interests, experiences, and unclassified). Further, we examined the depth and width of what bloggers self-disclosed to three target audiences (online audience, best friend, and parents), confirming that their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We operationalized the concept depth as the degree of personalized information shared in a social interaction in the VE. The levels of depth occur on a continuum, where level 1 indicated little to no personalization of information shared by the participant, and level 4 indicated that the participant shared highly personal information and acknowledged weaknesses related to T2D self-management [ 27 , 36 , 37 ]. Table 3 provides the definitions of each level of depth.…”
Section: Resultsmentioning
confidence: 99%
“…We operationalized the concept depth as the degree of personalized information shared in a social interaction in the VE. The levels of depth occur on a continuum, where level 1 indicated little to no personalization of information shared by the participant, and level 4 indicated that the participant shared highly personal information and acknowledged weaknesses related to T2D self-management [ 27 , 36 , 37 ]. Table 3 provides the definitions of each level of depth.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of early social networking was relatively simple but due to the widely used function of anonymity and the introduction of synchronous and asynchronous information transfer function, efficiency of users' self-disclosure has been drastically enhanced [9]. This development trend facilitates more frequent online exchanges of personal view, feelings, and private information among users [10]. Even interpersonal relationship development and maintenance are made possible via the cyberspace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The theory has been widely used in online social media contexts to examine one-to-one interaction (e.g. Cho, 2010;McEwan, 2011;Kim et al, 2012;Chen & Sharma, 2013;Limperos et al, 2014) and one-to-many communications (e.g., Thotho, 2010;Tang & Wang, 2012;Jin, 2013;Olson, 2013).…”
Section: Reasons For Disclosing Personal Information On Facebookmentioning
confidence: 99%